Perancangan Pengendalian Bahaya Pada PT. Alpha Graha Industri - Vincent Alexander Khosasi; Togar Wilater Soaloon Panjaitan (Jurnal Titra, 2023)
PT. Alpha Graha Industri is a company that produces alpha carts. There havebeen several work accidents at the production site of PT. Alpha Graha Industries. Thisfinal assignment was carried out using direct observation methods and interviews withcompany owners and local workers. The purpose of this final project is to reduce thenumber of work accidents at PT. Alpha Graha Industries. From the results of theanalysis that occurred, it was found that 22 activities in the production process had riskanalysis values of 59% high, 13.7% moderate and 27.3% low which could cause workaccidents. 32 risk control proposals have been proposed which are dominated by 50%technical engineering, 34.4% Personal Protective Equipment and 15.6% administration.The proposal given by the author has been approved by the company. It is predicted thatthe risk rating of the activities will be 100% low.